2020
DOI: 10.3390/cancers12030752
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Protein Synthesis and Proteasome Degradation Confers Sensitivity to Proteasome Inhibitor Bortezomib in Myc-Atypical Teratoid/Rhabdoid Tumors

Abstract: Atypical teratoid rhabdoid tumors (ATRTs) are among the most malignant brain tumors in early childhood and remain incurable. Myc-ATRT is driven by the Myc oncogene, which directly controls the intracellular protein synthesis rate. Proteasome inhibitor bortezomib (BTZ) was approved by the Food and Drug Administration as a primary treatment for multiple myeloma. This study aimed to determine whether the upregulation of protein synthesis and proteasome degradation in Myc-ATRTs increases tumor cell sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…This yielded 14 drugs with more-potent efficacy on MRTs versus Wilms tumor organoids. Among those were drugs previously identified as potential therapies for MRTs, such as histone deacetylase (HDAC) inhibitors, HSP90 inhibitors, and the proteasome inhibitor bortezomib (Carugo et al, 2019;Muscat et al, 2016;Tran et al, 2020). We also identified multiple mTOR inhibitors, which we previously described as having a cytostatic effect in MRTs (Custers et al, 2021).…”
Section: Drug Screening Of Mrt Organoids Reveals Tumor-and Patient-specific Drug Sensitivitiesmentioning
confidence: 85%
“…This yielded 14 drugs with more-potent efficacy on MRTs versus Wilms tumor organoids. Among those were drugs previously identified as potential therapies for MRTs, such as histone deacetylase (HDAC) inhibitors, HSP90 inhibitors, and the proteasome inhibitor bortezomib (Carugo et al, 2019;Muscat et al, 2016;Tran et al, 2020). We also identified multiple mTOR inhibitors, which we previously described as having a cytostatic effect in MRTs (Custers et al, 2021).…”
Section: Drug Screening Of Mrt Organoids Reveals Tumor-and Patient-specific Drug Sensitivitiesmentioning
confidence: 85%
“…Kai et al studied high-dose chemotherapy with SCT and found that it may contribute to a better outcome [27]. Proteasome inhibitors (Marizomib, carfilzomib, and bortezomib) were recently studied as potential targeted therapy for patients with AT/RT, and tumor models have shown promising results [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Although cisplatin-or carboplatin-based chemotherapy regimens have been used in many centers [4], we did not yet have a standardized chemotherapy protocol for AT/RT in Taiwan during the study period. The recent discovery of the preclinical activity of proteasome inhibitors in AT/RT [40,41], however, has encouraged us to initiate a multi-center phase II trial using a proteasome inhibitor as an add-on therapy to standard chemotherapy for newly diagnosed AT/RT. Thirdly, since AT/RT is a rare cancer and the number of cases is limited, the analysis of the relationship between tumor site, treatment type, and age group required that small groups (of less than five patients) be combined as a single unit.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted drugs for SHH pathway inhibitors have diverse therapeutic indications and have demonstrated efficacy for medulloblastoma‐SHH; such drugs should be investigated in the treatment of AT/RTs 70 . Tran et al 71 . reported that, compared with ATRT‐SHH cell lines, ATRT‐MYC cell lines were more sensitive to the proteasome inhibitor bortezomib.…”
Section: Molecular Targeted Therapies Of At/rtsmentioning
confidence: 99%
“… 70 Tran et al. 71 reported that, compared with ATRT‐SHH cell lines, ATRT‐MYC cell lines were more sensitive to the proteasome inhibitor bortezomib. They also found that survival was prolonged in ATRT‐MYC patient‐derived xenograft mice that received bortezomib, suggesting that bortezomib may function as targeted therapy for ATRT‐MYC.…”
Section: Molecular Targeted Therapies Of At/rtsmentioning
confidence: 99%